O ensino de história no Proeja: reflexões sobre o ensino integrado pelo viés da formação omnilateral - Becher, Paula Rochele Silveira (2017)
This dissertation sought to reflect the insertion, configuration and challenges of the teaching of History in technical courses offered from the institution of the National Program of Integration of Professional Education with Basic Education in the Youth and Adult Education (PROEJA). In order to reach this objective, firstly, a bibliographical survey has been carried out, situating historically and conceptually themes related to the Professional and Technological Education (EFA) and Youth and Adult Education (EJA) in the context of the demands and formulations of Brazilian educational public policies, as well as the perspectives on the teaching of History. Based on the proposed theoretical references, it was sought to understand how the teaching of History has been inserted in the courses offered by the said Program, in order to highlight the relevance of the production of knowledge of this discipline to the PROEJA public, as well as the challenges and perspectives that Permeate this insertion. To this end, two federal institutions of professional education were investigated in the central region of Rio Grande do Sul. One of them, the Industrial Technical School of Santa Maria, has been for more than fifty years as a technical school linked to the Federal University of Santa Maria. The other institution, the Farroupilha Federal Institute - Júlio de Castilhos Campus, was created from recent public policies, which instituted the Federal Institutes of Education, Science and Technology. In both institutions, in order to go beyond the aspects contained in the legislation that involves the object of this research, managers, teachers and students were heard. The conducting of semi-structured interviews with pedagogical managers and history teachers allowed a better understanding of the organization and the demands arising from these courses, which affect the organization of the teaching of History. To the students were given semi-open questionnaires that sought to understand the composition of the public that accesses the offered courses, as well as their expectations regarding them, the world of work and the teaching of History. Finally, it was understood that several challenges remain for the realization of integrated education by the bias of omnilaterality, capable of overcoming historical dichotomies of our society and, specifically, the constitution of Professional and Technological Education. However, the teaching of History may present itself as an important element for this overcoming, as it offers support for the structuring of historical consciousness.